2019
DOI: 10.1186/s13018-019-1470-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the effects of intermittent parathyroid hormone (1-34) by bone morphogenetic protein in a rat femoral open fracture model

Abstract: BackgroundNonunion in cases of open fracture is common. Both bone morphogenetic protein 2 (BMP-2) and parathyroid hormone (PTH) have been used to enhance bone healing. We investigated the combination of BMP-2 and PTH and examined the effects on a rat model of open femoral fractures.MethodsGroup I (n = 11) was implanted with control carrier. Group II (n = 12) was implanted with carrier containing 1 μg of recombinant human BMP-2 (rhBMP-2). Group III (n = 12) was implanted with carrier alone, followed by injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Fourth, we did not perform biomechanical testing that could quantify the degree of bony union. Instead, we evaluated bony union by the manual palpation method [13,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, we did not perform biomechanical testing that could quantify the degree of bony union. Instead, we evaluated bony union by the manual palpation method [13,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Manual palpation is a sensitive and speci c method of assessing bone fusion [13,21,22,23]. Manual palpation with varus/valgus and anterior/posterior angulated force was performed for all harvested specimens with a particular focus at the defect region.…”
Section: Manual Palpation and Manipulationmentioning
confidence: 99%
“…We previously reported that the synergistic effect of rhBMP-2 and PTH 1-34 administered systemically as a single dose at the optimal time was e cacious for fracture repair and signi cantly enhanced bone fusion in a rat femoral fracture model [22]. The purpose of this study was to clarify the optimal dosing interval and administration method for the combination of rhBMP-2 and PTH 1-34 in a rat spinal fusion model.…”
Section: Introductionmentioning
confidence: 98%
“…Bone healing is accelerated upon treatment with the parathyroid hormone in animal models 10 11 12) . Some studies also report the bone-healing potential of teriparatide, when used in human subjects who have vertebral or lower limb fractures 13 14 15 16 17) .…”
Section: Introductionmentioning
confidence: 99%